Management of Depression in Hemodialysis Patients: a Pilot Study - Mawaddah, Nurul; Mujiadi, Mujiadi; Wicaksono utomo, Robby (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: Depression is a common mental health problem in patients undergoing hemodialysis therapy. However, handling the problem of depression in the hospital has not become a treatment concern, resulting in increasing non-adherence to dialysis patient therapy. This study aims to determine the effect of depression management on the depression score of patients undergoing hemodialysis. Method: This study used pre-experimental designs with One Group Pretest-Posttest. The study was conducted at the Malang Regional Hospital. The study population was chronic kidney failure patients undergoing routine hemodialysis in the hospital, with the sample criteria for depression based on the Beck Depression Inventory-II instrument, using the simple random sampling technique obtained from a total of 40 respondents. Data were analyzed quantitatively by Wilcoxon Signed Rank Test. Results: There was an effect of depression management on the depression score of patients undergoing hemodialysis, and almost all respondents (92.5%) experienced a decrease in depression score. Providing depression management interventions carried out in 2 meetings was able to reduce depression scores.  Conclusions: Depression management has been shown to be effective in reducing depression in patients with all categories of depression, both mild, moderate, and severe depression to not depressed. Provision of interventions in the management of depression is necessary for patients who experience depression as a result of undergoing hemodialysis therapy to avoid non-adherence to therapy.